Diagnostic Delay of Spinal Tuberculosis Causing Medullary Compression - Corydon, Krestine; Ørum, Matilde Bjørn; Nøhr, Kristoffer Backman; Öbrink-Hansen, Kristina (Case Reports in Infectious Diseases, 2024)
We present a case of a Philippine woman in her late twenties, diagnosed with spinal tuberculosis after surgical intervention due to medullary compression. The diagnosis was preceded by four months of unexplained back pain. Differential diagnoses included ulcer, liver-gallbladder disease, musculoskeletal causes, and cancer. This case highlights the importance of considering tuberculosis as a differential diagnosis in patients from high-endemic areas to avoid diagnostic delay and the risk of disease progression.